Final answer:
For x>5, the equation without absolute value is y = 3x - 6, obtained by considering the signs of the expressions inside the absolute value brackets based on the condition given.
Step-by-step explanation:
The equation given is y=|x-3|+|x+2|-|x-5| and we are asked to rewrite it without absolute value for x>5.
Since x is greater than 5, we know that:
- x - 3 is positive, so |x-3| = x - 3.
- x + 2 is also positive, so |x+2| = x + 2.
- x - 5 is also positive, so |x-5| = x - 5.
Substituting the values back into the equation, we get:
y = (x - 3) + (x + 2) - (x - 5)
Simplifying, the equation becomes:
y = 3x - 6